2002
DOI: 10.1080/09639280210153290
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of student failure on an undergraduate accounting programme of study

Abstract: Academic failure creates financial and emotional issues for students, with associated resource and performance implications for higher education institutions. The literature reveals that much of the work on student performance is quantitative, restricting understanding of the deeper feelings and perceptions of students towards their studies. This paper explores undergraduate student performance from an experiential perspective, recognising the complexity and subjectivity of academic performance. Findings appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 14 publications
1
24
0
1
Order By: Relevance
“…Thus, the commitment of students to the ADO initiatives plays an important role towards the success of the academic development initiatives. These findings are supported by previous MCSER Publishing, Rome-Italy Vol 4 No 3 September 2013 721 researchers (Romer, 1993;Gracia & Jenkins, 2002;Fraser & Killen, 2003) who associated good academic success with factors such self-motivation, timely and regular examination preparation, and students' interest in class discussions. Variables such as the number of individual consultations (IC), gender (D1), the dummy variable for the year of 2009 are not statistically significant.…”
Section: Multiple Regression Analysissupporting
confidence: 76%
See 2 more Smart Citations
“…Thus, the commitment of students to the ADO initiatives plays an important role towards the success of the academic development initiatives. These findings are supported by previous MCSER Publishing, Rome-Italy Vol 4 No 3 September 2013 721 researchers (Romer, 1993;Gracia & Jenkins, 2002;Fraser & Killen, 2003) who associated good academic success with factors such self-motivation, timely and regular examination preparation, and students' interest in class discussions. Variables such as the number of individual consultations (IC), gender (D1), the dummy variable for the year of 2009 are not statistically significant.…”
Section: Multiple Regression Analysissupporting
confidence: 76%
“…In additon to this , at risk students were encouraged to attend lectures. Gracia & Jenkins(2002) emphasise that attendance is correlated with academic success.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Failure is an important and personal event in the life of a student (Gracia & Jenkins, 2002). According to Wicklund and Gollwitzer (1982), failures in educational life have significant effects on social and personal lives of the students.…”
Section: Introductionmentioning
confidence: 99%
“…It seems that the students who need to manage their time the best -the weaker students -are less prone to do so. The link may lay in the research of Gracia and Jenkins (2002). Gracia and Jenkins (2002, 103) found that, although students would accept responsibility for their failures, they were less willing to take control over their learning and expected someone else to do that.…”
mentioning
confidence: 99%